Preservice Teachers’ Argumentation and Some Relationships to Didactic-Mathematical Knowledge Features (2021)
RESUMEN: This paper presents research on the argumentation that preservice teachers perform when designing and teaching geometry. Argumentation is associated with speech acts carrying didactical intentions. This research study features of preservice teachers’ argumentation when explaining geometry tasks both to peers, during preparation and discussion of designed activities, and to students in the classroom. This is qualitative research and the results support establishing relationships between the didactical dimension of the didactic-mathematical knowledge model and some characteristics of the argumentation that preservice mathematics teachers exhibit during their planning and teaching.